Effects of testing parameters on the susceptibility to hydrogen embrittlement in precipitation-hardened nickel-based alloys: The role of continuous straining. (1st May 2022) - Martelo, D.F.; Maulana, Rd Panji; Leiva-garcia, R.; Joshi, G.R.; Morana, R.; Akid, R.
Abstract: The hydrogen embrittlement susceptibility of two precipitation hardened nickel-based alloys was studied. Conventional slow strain rate testing results are compared against data obtained from a modified Rising Step Loading Test with interrupted hydrogen charging to determine the role of defects in the passive layer caused by local straining. The results obtained in these tests, show that the elongation to failure for most cases was independent of the testing methodology. XPS and EIS studies indicate changes to the passive film structure caused by CP. These results imply that during hydrogen charging, the passive film is partially dissolved facilitating hydrogen uptake. Highlights: An interrupted H charging RSL technique was proposed to measure HE susceptibility. The HE resistance of two nickel alloys was compared using two testing techniques. Degradation of the passive layer after CP was observed using XPS and EIS. No direct correlation was found between ic, time to failure and global H content.